Analysis of the N-terminal region of human MLKL, as well as two distinct MLKL isoforms, reveals new insights into necroptotic cell death. Issue 1 (22nd January 2016) - Arnež, Katja Hrovat; Kindlova, Michaela; Bokil, Nilesh J.; Murphy, James M.; Sweet, Matthew J.; Gunčar, Gregor
Abstract : We show that mixed lineage kinase domain-like (MLKL) isoform 2, which lacks the pseudokinase domain and activation loop phosphorylation sites, is a more potent activator of cell death compared with MLKL isoform 1. Both MLKL isoforms are expressed in human monocyte-derived macrophages. Abstract : The pseudokinase mixed lineage kinase domain-like (MLKL) is an essential effector of necroptotic cell death. Two distinct human MLKL isoforms have previously been reported, but their capacities to trigger cell death have not been compared directly. Herein, we examine these two MLKL isoforms, and further probe the features of the human MLKL N-terminal domain that are required for cell death. Expression in HEK293T cells of the N-terminal 201 amino acids (aa) of human MLKL is sufficient to cause cell death, whereas expression of the first 154 aa is not. Given that aa 1–125 are able to initiate necroptosis, our findings indicate that the helix that follows this region restrains necroptotic activity, which is again restored in longer constructs. Furthermore, MLKL isoform 2 (MLKL2), which lacks much of the regulatory pseudokinase domain, is a much more potent inducer of cell death than MLKL isoform 1 (MLKL1) in ectopic expression studies in HEK293T cells. Modelling predicts that a C-terminal helix constrains the activity of MLKL1, but not MLKL2. Although both isoforms are expressed by human monocyte-derived macrophages at the mRNA level, MLKL2 is expressed at much lower levels. We propose that it may have a regulatory role in controlling macrophage survival, either in the steady state or in response to specific stimuli.